Urgensi Pengaturan Regulasi Penyelenggaraan Haji Furoda dalam Memberikan Perlindungan Hukum bagi Jemaah - Fitriyah Nurrahmah; Nabilla Farah Q.; Abel Reyhan I. (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2025)
Abstract This study analyzes the urgency of comprehensive regulation of furoda hajj in Indonesia. The high level of public interest in furoda hajj as an alternative to regular hajj is not matched by adequate legal protection and supervision. This has resulted in the vulnerability of furoda hajj pilgrims whose rights are not being fulfilled. Although Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah (PIHU Law) implicitly mentions the mujamalah visa as the basis for the implementation of furoda hajj, there are no regulations that comprehensively regulate the implementation of furoda hajj. This study uses a normative juridical research method with a statute approach and a conceptual approach. The legal sources of this study are classified into primary, secondary, and tertiary legal materials. The results of this study show the urgent need to formulate technical regulations for the implementation of furoda Hajj. The ideal regulatory model is built on three foundations, namely philosophical, juridical, and sociological foundations, which include guidance, service, and legal protection for furoda Hajj pilgrims. Keywords: Urgency; Regulation; Furoda Hajj; Legal Protection.